Informality as a generalized mode of urbanization: an autoethnography - Escalante, Mauricio Muñoz (Universidad de Boyacá, 2021)
Reflection paper on what urban informality means in Colombian academia. It uses autoethnography as qualitative research method. It doubts the accepted idea of various types of cities coexisting within the same urban center, being the majority of them different versions of informality. It argues that such atomization of the city, pigeonholing informality as a feature of poverty, allows urban theoreticians to avoid their responsibility. This manifests itself in the creation of a person, Us, which stands outside of Them, the academic peers of developed countries, and of You, the inhabitants of those out-of-all-order cities. It proposes that informality is a way of making the city, even by Us, who pretend to live away from it.